Videogames are for boys: male gaming as an anti-gender identity - Romero-Medina, Pablo (Historia y Comunicación Social, 2025)
The videogame industry is the most important cultural and entertainment industry of our times with 3,2 billion players worldwide and with a social and cultural impact in every aspect of our lives. The industry itself has historically been constructed as a masculinist space where geek masculinity was the role model to follow. In this work we propose to analyse how the masculinist culture that developed this space have generated an affinity between a sector of the gaming community and the anti-gender groups from the manosphere. We will study the creation of the gamer identity as an anti-gender identity that it´s born from a rhetoric of victimhood and betrayal that is normal on current far-right wing forces. La industria del videojuego es la industria cultural y del entretenimiento más importante de nuestros días, con 3.200 millones de jugadores en todo el mundo y con un impacto social y cultural en todos los aspectos de nuestras vidas. La propia industria se ha construido históricamente como un espacio masculinista en el que la masculinidad geek era el modelo que seguir. En este trabajo nos proponemos analizar cómo la cultura masculinista que ha desarrollado este espacio ha generado una afinidad entre un sector de la comunidad de jugadores y los grupos anti-género de la esfera masculina. Estudiaremos la creación de la identidad gamer como una identidad anti-género que nace de una retórica de victimismo y traición que es normal en las actuales fuerzas de extrema derecha.